Research on VR Applications Based on Computer Technology - Lin, Zizhi (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the continuous progress of the era of science and technology and the increasing abundance of technology products, the influence of VR technology has attracted increasing attention, and people are constantly exploring the uses and possibilities of VR. The evolution history of virtual reality technology can be divided into four stages, and the simulation of sound shape dynamics is the first stage containing the idea of virtual reality. Virtual reality germination is the second stage. The emergence of virtual reality concept and theory is the third stage. The further improvement and application of virtual reality theory is the fourth stage. This paper uses the role of computer technology in VR, and discusses the application of computer in VR and the work that VR can be realized or carried out, such as VR games or use Virtual reality in medical health,even in comprehensive application in urban governance.As well as the current development problems and the prospects for the future.Like Technical restrictions, high hardware costs and Virtual reality content is relatively less represented in various fields.